Associative effects of wet distiller's grains plus solubles and tannin-rich peanut skin supplementation on in vitro rumen fermentation, greenhouse gas emissions, and microbial changes1. (11th October 2019) - Min, Byeng Ryel; Castleberry, Lana; Allen, Heather; Parker, David; Waldrip, Heidi; Brauer, David; Willis, William
Abstract: Two sets of in vitro rumen fermentation experiments were conducted to determine effects of diets that included wet distiller's grains plus solubles (WDGS ) and tannin-rich peanut skin (PS ) on the in vitro digestibility, greenhouse gas (GHG ) and other gas emissions, fermentation rate, and microbial changes. The objectives were to assess associative effects of various levels of PS or WDGS on the in vitro digestibility, GHG and other gas emissions, fermentation rate, and microbial changes in the rumen. All gases were collected using an ANKOM Gas Production system for methane (CH4 ), carbon dioxide (CO2 ), nitrous oxide (N2 O), and hydrogen sulfide (H2 S) analyses. Cumulative ruminal gas production was determined using 250 mL ANKOM sampling bottles containing 50 mL of ruminal fluid (pH 5.8), 40 mL of artificial saliva (pH 6.8), and 6 g of mixed diets after a maximum of 24 h of incubation. Fermenters were flushed with CO2 gas and held at 39 °C in a shaking incubator for 24 h. Triplicate quantitative real-time polymerase chain reaction (qPCR) analyses were conducted to determine microbial diversity. When WDGS was supplied in the diet, in the absence of PS, cumulative CH4 production increased ( P < 0.05) with 40% WDGS. In the presence of PS, production of CH4 was reduced but the reduction was less at 40% WDGS. In the presence of PS, ruminal lactate, succinate, and acetate/propionate (A/P ) ratio tended to be less with a WDGS interaction ( P < 0.01). In the presence of PS and with 40% WDGS, average populations of Bacteroidetes, total methanogens, Methanobrevibacter sp. AbM4, and total protozoa were less. The population of total methanogens ( R 2 = 0.57; P < 0.01), Firmicutes ( R 2 = 0.46: P < 0.05), and Firmicutes/Bacteroidetes (F/B ) ratio ( R 2 = 0.46; P < 0.03) were strongly correlated with ruminal CH4 production. Therefore, there was an associative effect of tannin-rich PS and WDGS, which suppressed methanogenesis both directly and indirectly by modifying populations of ruminal methanogens.